Flagellin/NLRC4 Pathway Rescues NLRP3-Inflammasome Defect in Dendritic Cells From HIV-Infected Patients: Perspective for New Adjuvant in Immunocompromised Individuals - Reis, Edione Cristina dos; Leal, Vinícius Nunes Cordeiro; Soares, Jaíne Lima da Silva; Fernandes, Fernanda Pereira; Souza de Lima, Dhêmerson; de Alencar, Bruna Cunha; Pontillo, Alessandra (Frontiers in Immunology, 2019)
Introduction: NLRP3 inflammasome plays a key role in dendritic cells (DC) activation in response to vaccine adjuvants, however we previously showed that it is not properly activated in DC from HIV-infected patients (HIV-DC), explaining, at least in part, the poor response to immunization of these patients. Taking in account that several cytoplasmic receptors are able to activate inflammasome, and that bacterial components are considered as a novel and efficient adjuvant, we postulated that bacterial flagellin (FLG), a natural ligand of NAIP/NLRC4 inflammasome, could rescue the activation of the complex in HIV-DC. Objective: Demonstrate that FLG is able to activate monocyte-derived dendritic cells from HIV-infected individuals better than LPS, and to what extent the entity of inflammasome activation differs between DC from HIV-infected patients and healthy donors. Methods: Monocyte-derived dendritic cells from HIV-infected patients (HIV-DC) and healthy donors (HD-DC) were stimulated with FLG, and inflammasome as well as DC activation (phenotypic profile, cytokine production, autologous lymphocytes activation) were compared. Chemical and genetic inhibitors were used to depict the relative contribution of NLRC4 and NLRP3 in HIV/HD-DC response to FLG. Results: FLG properly activates HD-DC and HIV-DC. FLG induces higher inflammasome activation than LPS in HIV-DC. FLG acts through NLRC4 and NLRP3 in HD-DC, but at a lesser extent in HIV-DC due to intrinsic NLRP3 defect. Conclusions: FLG by-passes NLRP3 defect in HIV-DC, through the activation of NAIP/NLRC4 inflammasome, indicating possible future use of the bacterial component as an efficient adjuvant in immunocompromised individuals.